Medical partnerships for improved patients’ outcomes—are they working? - Grouse, Lawrence (Journal of Thoracic Disease; Vol 6, No 5 (May 08, 2014): Journal of Thoracic Disease, 2014)
To improve patients’ outcomes, ICC believes that there must be effective partnerships between the four key medical groups whose efforts are needed to benefit patients (Figure 1). The first group includes patient organizations. Patients should let people know what they need, and they need to be represented by patient organizations and patient advocates when decisions are made that affect patients. We should remember that the main reason that medical companies and organizations exist is to improve the welfare of patients. It is a point that is sometimes neglected.